Alternative concepts for a global financial system : an answer to the present world financial crisis - Fuders, Felix (Estudios Internacionales, 2010)
Neither interest-capitalism nor communism are natural economic forms, that is, they do not match human nature, but rather are forced by government, meaning that both are destined to fail. Communism leads to laziness and neo-liberalism to greed. In a healthy, that is, natural economic system, neither a planned economy nor interest exist, both of which lead to constrain freedom. With communism, people are enslaved through the forced labour inherent in a planned economy; in an interestbased economy, people are enslaved through the burden of interest, which multiplies exponentially and eventually makes it impossible for an economy to supply households sufficiently, since the exponentially multiplying interest must be earned and paid for.